EJB 3 in Action - Panda, Debu; Rahman, Reza; Lane, Derek (Manning Publications, 2007)
EJB 3 is the most important innovation introduced in Java EE 5.0. EJB 3 promises to simplify enterprise development, abandoning the heavyweight EJB 2.x model in favor of a lightweight POJO framework. The API represents a lot of hard work, honest introspection, and a fresh perspective on EJB, all without sacrificing the mission of enabling business application developers to create robust, scalable, standards-based solutions. In the tradition of Manning's In Action series, this book tackles the subject matter head-on, through numerous code samples, real-life scenarios, and illustrations. It is geared toward helping you learn EJB 3 quickly and easily. The authors make the subject matter approachable, covering the basics where needed as well as providing guidance, deep coverage, and best practices. The book highlights what EJB 3 has to offer without disregarding the contributions and strengths of seminal technologies like Spring, Hibernate or TopLink. What's Inside * Building Business Logic with POJO Session Beans and Message Driven Beans * EJB 3 Dependency Injection and Interceptors * Domain Modeling and Object-Relational Mapping with the EJB 3 Java Persistence API * Effectively manipulating and retrieving entities, including using the Java Persistence Query Language * Using EJB 3 from other tiers (such as the web or application client tier) and frameworks such as Spring * Best practices, performance tuning, and design patterns * Migrating from EJB 2.x and other POJO frameworks